2015
DOI: 10.1111/gec3.12203
|View full text |Cite
|
Sign up to set email alerts
|

Gentrification, Transit, and Land Use: Moving Beyond Neoclassical Theory

Abstract: Despite attention to social equity in the way public transit services are distributed, little work has considered how transportation systems may impact social equity through land use changes, particularly gentrification. Existing research on transportation and land use has been grounded primarily in a neoclassical urban economic perspective. However, the neoclassical framework is limited in its ability to handle issues of social justice such as the gentrification process. Meanwhile, critical gentrification lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…In contrast, the Marxistderived "rent gap" theory explains capital investments and subsequent gentrification based on the higher underlying location land value in otherwise declining areas. Although this process normally occurs regardless of the presence or absence of a transit line, it has been argued that enlargements of pre-existing rent gaps might result from the opening of new lines and/or local TOD development projects (Revington, 2015). As the rent gap expands, real estate investments increase as they become more profitable, thus leading to declining affordability and the consequent up-filtering of households.…”
Section: The Hypothesis Of Tod-related Gentrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the Marxistderived "rent gap" theory explains capital investments and subsequent gentrification based on the higher underlying location land value in otherwise declining areas. Although this process normally occurs regardless of the presence or absence of a transit line, it has been argued that enlargements of pre-existing rent gaps might result from the opening of new lines and/or local TOD development projects (Revington, 2015). As the rent gap expands, real estate investments increase as they become more profitable, thus leading to declining affordability and the consequent up-filtering of households.…”
Section: The Hypothesis Of Tod-related Gentrificationmentioning
confidence: 99%
“…Relying on compact, transit-oriented growth patterns around train, light-rail or metro stations, TOD aims to promote a modal shift and reduce automobile dependence, while also enhancing neighbourhoods' liveability, which is a multidimensional and rather vague concept encompassing healthy, safe, and comfortable environments, quality and aesthetics of public spaces, as well as expanded social and economic opportunities (for a comprehensive definition, see Southworth, 2003). However, TOD might also induce gentrification and concomitant low-income group displacement, and some researchers and public advocates have expressed concerns regarding the social costs and fairness of sustainability-driven approaches (Rayle, 2015;Revington, 2015). Since TOD creates conditions for real estate investment, land values are expected to increase, thus potentially leading to restrictions for low-income groups with regards to accessing housing and maintaining their residential locations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the city of Curitiba intentionally increased urban density along the BRT corridors of the city, promoting a pioneering form of transit oriented development already in the late 1960s [46][47][48]. The second is the case for increased land values, which often originate forms of gentrification around transport corridors-a phenomenon that has been investigated in different settings [49][50][51][52]. The arrival of more affluent groups who replace previous inhabitants is especially problematic for socially focused transport policies, whose potential beneficiaries may be expulsed and forced to move to cheaper areas with poorer levels of accessibility.…”
Section: Urban Mobility and Socio-spatial Concerns: An Analytical Framentioning
confidence: 99%
“…Revington (:152) observed that, while gentrification is considered to be an intrinsically inequitable process, public transport has always been conceived as a way to promote social equity, by opening up the access to the space of the city and its opportunities to residents of all classes. What is the relation between policies of transport improvement and gentrification dynamics?…”
Section: Understanding the Link Between Gentrification And Transport mentioning
confidence: 99%
“…As Revington (:157) underlined, interventions on transport infrastructure “alter the distributions of locational advantages” within the city, and households with higher incomes are better able to compete for the new locational benefits, while low‐income households may be priced out due to the rent capitalization effect—a process which has been widely documented in urban economic studies (e.g., Ahlfeldt ; Ahlfeldt and Wendland ; Bartholomew and Ewing ; Baum‐Snow and Kahn ; Bowes and Ihlanfeldt ). A few authors (see Kahn ; Lin ; Pollack et al.…”
Section: Understanding the Link Between Gentrification And Transport mentioning
confidence: 99%